Parental Perceptions on the Concept of Children’s Play in Preschool in Insein Township, Yangon, Myanmar - Tun, Win Ei Phyu; Pransiska, Rismareni (EDUMALSYS Journal of Research in Education Management, 2023)
This study has been carried out to determine the Parents’ Perceptions of Children’s Play in Preschool in Insein Township, Yangon City, Myanmar. The subjects of this study were preschool parents who lived in the area. This research was done through a descriptive quantitative method with 40 populations. The sample of this study was 40 parents chosen by using the total sampling method. The research instruments were questionnaires. The questionnaires consist of 20 statements with three different parts; General Perceptions of parents on Children’s Play, Parents’ Perceptions of children’s play at home, and Parents’ Perceptions of children’s play in Preschool. Data was collected using an online survey. The questionnaires are made in Google Forms and the link was sent to the participants. Data analysis was done in a quantitative approach by giving scores to each answer. Based on the research analysis, it was found that generally, parents have positive perceptions of children’s play with a percentage of 90.7%. Yet, Mothers outweigh to value the importance of play contrasted to Fathers with scores of 91% and 83% respectively.